2013
DOI: 10.1002/jip.1392
|View full text |Cite
|
Sign up to set email alerts
|

Testing Existing Classifications of Serial Murder Considering Gender: An Exploratory Analysis of Solo Female Serial Murderers

Abstract: Serial murder is a genre of crime that has received a great deal of media and academic attention, yet, serial murder committed by women has only begun to garner a portion of this attention within the last 15 years. This study examines the reliability of Kelleher and Kelleher's classification rubric, the only classification system developed for female serial murderers, as well as considering Hickey's classification of serial offenders by location. Other variables associated with homicide research have also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Evidence suggests that hedonistic serial killers are the most prevalent of all female serial offenders. They seek profit, comfort, and/or thrill, and target relatives or those that are particularly vulnerable, such as children or the elderly (Farrell et al, 2013;Holmes et al, 1991). Our data are consistent with this, as financial gain/comfort was the motive of nearly half of FSKs in our sample.…”
Section: Caveats To Classifying Fsks By Motivesupporting
confidence: 86%
See 1 more Smart Citation
“…Evidence suggests that hedonistic serial killers are the most prevalent of all female serial offenders. They seek profit, comfort, and/or thrill, and target relatives or those that are particularly vulnerable, such as children or the elderly (Farrell et al, 2013;Holmes et al, 1991). Our data are consistent with this, as financial gain/comfort was the motive of nearly half of FSKs in our sample.…”
Section: Caveats To Classifying Fsks By Motivesupporting
confidence: 86%
“…They also have different motives and use different means for killing (Hickey, 2010), ranging from smothering their own children, to killing successive spouses for insurance money, to acting as 'angels of death' administering lethal injections to helpless people in their care. Because FSKs diverge from male serial killers' modi operandi in their crimes, it is important to note that, as Farrell, Keppel, and Titterington (2013) contend, FSKs are not easily categorized into the dimensions developed from extensive study of male serial killers. It is prudent, then, to see what information can be yielded with a larger, more current sample of FSKs.…”
Section: Previous Researchmentioning
confidence: 99%
“…This project has taken the field a step further, highlighting the shortfalls found in our current system of classifying female serial killers based solely on their motivation for murder. As these data demonstrate, and consistent with recent work by Farrell et al (2013), the motivations for female serial homicide offenders are often complex and may differ from one victim to the next. As such, it is important to move beyond this style of classification and to instead focus on the personality features unique to female serial killers.…”
Section: Discussionsupporting
confidence: 86%
“…Recent research attempting to utilize this classification system encountered similar difficulties. Farrell et al (2013) attempted to apply the Kelleher and Kelleher typology to ten identified female solo serial murderers and found that their sample could not be classified based on motivations alone. Based on their findings, Farrell et al advocate for a new classification system focusing on the more objective elements of a murder, "such as a combination of the victim-offender relationship and the manner the offender uses to approach her victim" (2013, p. 285).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation